CULTURE RELATIONSHIPS BETWEEN SERBIA NAD JAPAN: AN INTERNET RESEARCH (Heritage, 2020)
Paper present Internet research into culture relationships between Serbia and Japan. The research has been conducted within the framework of available digital tools that allow for insights into culture relationships between Japan and geographical area of Republic of Serbia, but not between Japan and integral Serbian culture area, and in this regards the paper is specific call for action for such tools to be produced in the future that will provide for possibilities for scientific research and insights into complete sphere of relationships between Serbian culture area and other cultures and peoples. Paper presents the research into historic newspapers based on keyword searchable digital library pretraziva.rs , newspaper archives Ebart and Google services of Advanced search and Google Trends. All the results point into the direction of establishing the fact that strong culture relations exist between Japan and Serbia from the end of 19th century until today. Paper shows that these relationships follow the path of development of technological basis that grounds communication among two peoples and two cultures, and comparative analysis of relationships with other nations and states show that relationships between Japan and Serbia have unusual high level considering geographical distance and traditional gap between these two cultures in the centuries before the period of globalization allowed for their meeting, mixing and mutual influences.
Keywords: Culture relations, Serbia, Japan, Internet research, Serbian culture area, Historic newspapers.